THE ROLE OF SELF-CONSTRUAL AND GOAL ORIENTATION ON EMPLOYEE INNOVATIVE WORK BEHAVIOR - Frislia, Ernie; Handoyo, Seger (Faculty of Psychology, Diponegoro University, 2020)
Innovation is an effort to increase the companies' competitiveness in Indonesia in the era of the ASEAN Economic Community and confront the fourth industrial era. Innovative work behavior is an organization's methods to implement innovations and improve performance, excellence, competitiveness, and confront changes in the dynamic external environment. This study aims to examine the effect of self-construal and goal orientation on innovative work behavior by testing hypotheses using multiple regression analysis. Data collection in this study uses an innovative work behavior scale, self-construal scale, and goal orientation scale, an online survey method filled by 168 employees working in the manufacturing industry sectors in Indonesia. The results show that self-construal and goal orientation have a positive effect on innovative work behavior, enhancement in self-construal, and goal orientation to increase employees' innovative work behavior—the contribution of goal orientation significant higher for employees' innovative work behavior than for self-construal contributions. Individuals with goal orientations can help organizations to develop innovation through innovative work behavior.